Structural insights into the biological functions of the long pentraxin PTX3 - Massimino, Anna Margherita; Colella, Filippo Emanuele; Bottazzi, Barbara; Inforzato, Antonio (Frontiers in Immunology, 2023)
Soluble pattern recognition molecules (PRMs) are a heterogenous group of proteins that recognize pathogen-and danger-associated molecular patterns (PAMPs and DAMPs, respectively), and cooperate with cell-borne receptors in the orchestration of innate and adaptive immune responses to pathogenic insults and tissue damage. Amongst soluble PRMs, pentraxins are a family of highly conserved proteins with distinctive structural features. Originally identified in the early 1990s as an early inflammatory gene, PTX3 is the prototype of long pentraxins. Unlike the short pentraxin C reactive protein (CRP), whose expression is mostly confined to the liver, PTX3 is made by several immune and non-immune cells at sites of infection and inflammation, where it intercepts fundamental aspects of infection immunity, inflammation, and tissue remodeling. Of note, PTX3 cross talks to components of the complement system to control cancer-related inflammation and disposal of pathogens. Also, it is an essential component of inflammatory extracellular matrices (ECMs) through crosslinking of hyaluronic acid and turn-over of provisional fibrin networks that assemble at sites of tissue injury. This functional diversity is mediated by unique structural characteristics whose fine details have been unveiled only recently. Here, we revisit the structure/function relationships of this long pentraxin in light of the most recent advances in its structural biology, with a focus on the interplay with complement and the emerging roles as a component of the ECM. Differences to and similarities with the short pentraxins are highlighted and discussed.